PEMANFAATAN CAMPURAN MORTAR DAN PARTIKEL KAYU SEBAGAI ELEMEN INTI BALOK BETON KOMPOSIT - Maricar, Shyama; Nirmalawati, Nirmalawati; Rivani, Agus (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2014)
Lightweight concrete has ability to increase workability and reduce structure load such as gravity and earthquake loads. Therefore lightweight and adequately rigid structural system is required. Based on efficiency of material application and adaptation optimization to the stress distribution system, composite system become one alternative that can be utilize, especially on beam structure. In this case, collaboration between lightweight concrete and ordinary concrete will be the deciding factor to achieve the objectives mentioned above. To construct lightweight concrete, timber particles obtained from sawmill industrial waste with density of 0,35 – 0.65 gr/cm3 will be highly possibly to utilize. This research aims to obtain the composition of concrete and timber particles mix that its strength can be measured in order to get effective composite concrete beam. A number of tests to the mix of concrete and timber particles were conducted to find out its pressure strength, tensile strength and elasticity, in order to get the percentage of timber particles used in concrete that will be used to create composite concrete with ordinary concrete. Sawmill and furniture industrial waste in form of timber particles can be utilized as material to create lightweight concrete which was limited only to nonstructural element. Keyword : Normal/Ordinary concrete,mortar concrete ,coconut timber particles